Exploratory and confirmatory factor analysis of values-about-self among 2nd Year High School students of New Era University - Magdael, Michael G (2005)
Abstract (This paper is an Exploratory and Confirmatory investigation of Values-About-Self (VAS) among second year high school students of New Era University whose sections were taken randomly from the twelve sections of second year high school students. The VAS Scale developed by Baybay was used and confirmed by the researcher. Confirmatory Factor Analysis was carried out using Baybays BAS model and the test results indicated lack-of-it of the hypothesized model. Thus, the data on the students of the four sections of second year high school students of New Era University did not fit on Baybays Vas model. Using Exploratory Factor Analysis with Promax Rotation of factor structure, five-factor model was formed after examining the competing models. The researcher named the new factors as: positive action, initiative insistence, artistic participation, creative well being, and self-motivation. This new VAS model had better statistical properties. The five factor model or new VAS model was also subjected to Confirmatory Factors Analysis and the results indicated a good model fit. Thus, the data on the students of the four sections of second year high school students of NEU did fit on the new VAS model. Using Baybays factor model, MANOVA was performed on mean scores on VAS and VEG, with gender, family structure, parental presence, peer relation, and academic achievement as grouping variables. Family structure, parental presence, peer relation were not significant in explaining differences in the mean scores of VAS and VEG of the respondents on the other hand, mean scores on VAS and VEG differ significantly with respects to gender and academic achievement. Using the new VAS model, MANOVA was performed on mean scores on VAS and VEG, with gender, family structure, parental presence, peer relation, and academic achievement as grouping variables. Family structure,parental presence, peer relation were not significant in explaining differences in the mean scores of VAS and VEG of the respondents. On the other hand, mean scores on VAS and VEG differ significantly with respects to gender and academic achievement).
Vita.
Thesis ( M.S. Statistics)--University of the Philippines, Diliman.
Keywords: Factor analysis; Estimation theory